The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1371/journal.pone.0281038
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of early initiation of first antenatal care visit in Ethiopia based on the 2019 Ethiopia mini-demographic and health survey: A multilevel analysis

Abstract: Background Early initiation of the first antenatal care visit provides a critical opportunity for health promotion, disease prevention, and curative care for women and their unborn fetuses. However, in developing countries, including Ethiopia, it is underutilized and most of the pregnant women didn’t attend antenatal care visits during the first trimester (early). Therefore, the objective of this study was to estimate the prevalence of early initiation of antenatal care visits and its determinants among reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Women with low levels of education are more likely to initiate ANC late than women with higher levels of education. These findings are comparable to those reported by other researchers [11,24,25,27,28,[32][33][34]36,48,50,51,53]. Three reasons may be suggested as explanations for why uneducated women are likely to initiate ANC late.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Women with low levels of education are more likely to initiate ANC late than women with higher levels of education. These findings are comparable to those reported by other researchers [11,24,25,27,28,[32][33][34]36,48,50,51,53]. Three reasons may be suggested as explanations for why uneducated women are likely to initiate ANC late.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies conducted in Malawi have reported regional differences in the utilization of maternal health services. In addition, studies conducted in Burkina Faso [50], Ethiopia [11,42], Ghana [22], Nigeria [27,51] and Sierra Leone [52] have reported regional differences in the initiation of ANC. Two factors could be responsible for the observed regional differences in the late initiation of ANC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation